Motivation to Learn Mathematics After the Covid-19 Pandemic Students - Rohmawati, Sinta; In'am, Akhsanul; Zukhrufurrohmah, Zukhrufurrohmah (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
During the COVID-19 pandemic, most students were not motivated to learn because learning was online. After the end of the COVID-19 pandemic, students returned to learning offline, causing changes in students' learning motivation. Thus, this research aims to determine the level of students' mathematics learning motivation after the COVID-19 pandemic by describing students' mathematics learning motivation based on motivation indicators. The research method used is a quantitative approach with a descriptive type. The respondents of this research were 110 class VII students of SMP Negeri 1 Bangsal, Mojokerto Regency, East Java. The data collection technique used was an online questionnaire in the form of a Google Form containing 36 statement items. The data analysis technique used is descriptive analysis. The results of this research data analysis show that students' mathematics learning motivation in the high category is 72%, medium is 21%, and low is 7%. It can be concluded from the results of the analysis that the mathematics learning motivation after the COVID-19 pandemic for class VII students is in the high category, which means that the 5 indicators of mathematics learning motivation are met well. The indicator with the highest average of 4.09 is the task value indicator.